International Trade Outlook for Latin America and the Caribbean 2018 - Caribbean, Economic (United Nations, 2019)
This edition of International Trade Outlook for Latin America and the Caribbean covers 2018 and is divided into three chapters. Chapter I analyses the impact of divergent global growth and trade tensions on trade in the region. Chapter II examines the share of Latin America and the Caribbean in global trade in minerals and metals. The region overall is a net exporter in this sector; however, given the typically low level of processing of its exports, it has the largest share in this category of primary products of all regions in the world. Finally, Chapter III examines whether cross-border e-commerce has the potential to galvanize and diversify exports from the region. Cross-border e-commerce refers to transactions for products and services that are ordered online, platform-enabled, or delivered online.